Development of Parenting FoMO Scale on Parents Using Social Media - Widhyasetyanti, Ghaisani; Febrianti, Rianda; Wulandari, Astri; Yuniar, Yuniar; Seniati, Ali Nina Liche (Universitas Medan Area, 2024)
This study aimed to develop a Parenting FoMO scale on parents using social media in Indonesia. Parenting FoMO is measured through four dimensions: missed experience, compulsion, comparing with others, and being left out. This study involved 115 parents using social media with children aged below 18 years old. Analysis methods used were Cronbach Alpha to examine reliability, analysis item using Corrected-Item Total Correlation (CrIT) and factor loading with Confirmatory Factor Analysis (CFA) to examine validity. Results exhibit that the Parenting FoMO scale is valid and reliable for measuring Parenting FoMO on parents using social media.